Deep-water octocorals (Cnidaria: Octocorallia) from Brazil: Family Chrysogorgiidae Verrill, 1883 - Cordeiro, Ralf T. S.; Castro, Clovis B.; Pérez, Carlos D. (Zootaxa, 2015)
Current knowledge about the Brazilian deep-water octocoral fauna remains scarce, fragmented, and mostly based on unpublished, regional scale surveys. The present work provides the first comprehensive study of the family Chrysogorgidae Verrill, 1883 in Brazil, based on morphological analysis of specimens collected in the last decade and those currently placed in museums. Members of this family are common mainly at great depths and remarkable for the iridescent aspect of their colonies. In Brazil, to the present, only four species were reported: Chrysogorgia elegans (Verrill, 1883), Chrysogorgia multiflora Deichmann, 1936, Stephanogorgia rattoi Castro, Medeiros & Loiola, 2010 and Trichogorgia brasiliensis Castro, Medeiros & Loiola, 2010—the last two are shallow-water species. In this study, three new deep-water species are described, Chrysogorgia tuberculata, Chrysogorgia upsilonia and Radicipes kopelatos, and a new record to Brazil is reported, Chrysogorgia fewkesii Verrill, 1883, as well as latitudinal expansions in distributions of Chrysogorgia elegans and Chrysogorgia multiflora are presented.